Mastering VMware Horizon 7 : learn advanced virtualization techniques and strategies and dive deeper into VMware Horizon 7, take responsibility for optimizing your organizations resources! /: learn advanced virtualization techniques and strategies and dive deeper into VMware Horizon 7, take responsibility for optimizing your organizations resources!. (2016) - Oven, Peter von; Coombs, Barry
No abstract available